Transcriptomic and metabolomic characterization of antibacterial activity of Melastoma dodecandrum - Poh, Wee Han; Ruhazat, Nur Syahirah; Yang, Lay Kien; Shivhare, Devendra; Lim, Peng Ken; Kanagasundaram, Yoganathan; Rice, Scott A.; Mutwil, Marek (Frontiers in Plant Science, 2023)
Antibacterial resistance poses a significant global threat, necessitating the discovery of new therapeutic agents. Plants are a valuable source of secondary metabolites with demonstrated anticancer and antibacterial properties. In this study, we reveal that Melastoma dodecandrum exhibits both bacteriostatic and bactericidal effects against Pseudomonas aeruginosa and Staphylococcus aureus. Treatment with plant extracts results in membrane damage and a reduction in P.aeruginosa swimming and swarming motility. A comparative analysis of bacterial transcriptomes exposed to M.dodecandrum extracts and four distinct antibiotics indicates that the extracts may trigger similar transcriptomic responses as triclosan, a fatty acid synthesis inhibitor. Activity-guided fractionation suggests that the antibacterial activity is not attributable to hydrolyzable tannins, but to unidentified minor compounds. Additionally, we identified 104 specialized metabolic pathways and demonstrated a high level of transcriptional coordination between these biosynthetic pathways and phytohormones, highlighting potential regulatory mechanisms in plant metabolism in M.dodecandrum.